Effects of carbonate alkalinity on branchial gene expression in the large-scale loach (Paramisgurnus dabryanus) - Huang, Mei; Wu, Meng-Xiao; Zhang, Lin-Jiang; Mi, Di; Zhang, Yun-Long (Frontiers in Marine Science, 2022)
Improving the knowledge on alkaline tolerance mechanism in fresh teleosts is beneficial for developing commercial saline-alkali aquaculture. The large-scale loach (Paramisgurnus dabryanus) may be a viable aquacultural species for saline-alkaline water, however, the defensive mechanisms of this species to alkaline water are still scarce. For this purpose, fish were exposed to 40, 50, and 60 mmol L-1 NaHCO3 solution for 12, 48, and 96 h to evaluate the branchial transcriptional changes of Rhesus (Rh) glycoproteins, Aquaporins (Aqp)1 and Aqp3. With longer exposure times, there was a noticeable increase in the Rhag transcript levels. A considerable rise in Rhag expression was likewise brought on by high carbonate alkalinity during various NaHCO3 exposure duration. Various periods of carbonate alkalinity exposure induced a significant decline in Rhbg mRNA level. A markedly up-regulation of Rhcg was observed after various periods of alkalinity exposure in the gills of large-scale loach. During 60 mmol L-1 NaHCO3 exposure, carbonate alkalinity induced a significant up-regulation of aqp1 in the gills of large-scale loach. In contrast, aqp 3 expression was found to be significantly lower in the gills of large-scale loach after 48 hours of 60 mmol L-1 NaHCO3 exposure. The current findings revealed that under high alkalinity exposure, the large-scale loach upregulated Rhag and Rhcg to enhance NH3 efflux out of the gills. Additionally, it has been proposed that this species maintains proper osmolality to adapt to an alkaline environment by down-regulating aqp3 to impede urea removal and up-regulating aqp1 in the gills to excrete excessive internal water.